Analisis Makna Puisi “Penunggu Gunung Berapi” Karya W.S. Rendra: Kajian Semiotik Barthes: Penelitian - Kadir, Herson (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Poetry is a poet's interpretation of life, the use of diction rich in meaning in poetry is an important element that gives aesthetic value to literary works. One poem that describes a deep meaning and deserves to be explored in a complex way is "Volcano Guardian" by W.S. Rendra. W.S. Rendra's poem, "Volcano Guardian," offers an exploration of significant values, such as the relationship between humans and nature, power, and death. This study uses a qualitative approach using a descriptive approach. Roland Barthes' semiotic theory offers a very relevant analytical framework for studying the poem "Volcano Guardian" by W.S. Rendra. identification and recording of relevant data, especially elements of the text that can be interpreted based on Barthes' five codes (hermeneutic, semic, symbolic, proairetic, and gnomic). This study proves that Roland Barthes' semiotic approach is effective in revealing the depth of meaning and theme in the poem "Penunggu Gunung Berapi". The poem not only depicts the physical landscape, but also explores universal themes such as alienation, longing, the search for meaning, and the relationship between humans and nature. The use of the five semiotic codes provides a comprehensive and multi-dimensional interpretation of this literary work.